Two New Diterpenoids Formed by Transannular Diels–Alder Cycloaddition from the Soft Coral Sarcophyton tortuosum, and Their Antibacterial and PPAR-β Agonist Activities - Min Sun; Songwei Li; Jianang Zeng; Yuewei Guo; Changyun Wang; Mingzhi Su (Marine Drugs)
Two new cembrane-derived tricyclic diterpenes belonging to the sarcophytin family, namely 4a-hydroxy-chatancin (1) and sarcotoroid (2), together with two known related ones (3 and 4), were isolated from the soft coral Sarcophyton tortuosum collected off Ximao Island in the South China Sea. The structures of the new compounds were elucidated by extensive spectroscopic analysis, a quantum mechanical nuclear magnetic resonance (QM-NMR) method, a time-dependent density functional theory electronic circular dichroism (TDDFT-ECD) calculation, X-ray diffraction analysis, and comparison with the reported data in the literature. A plausible biosynthetic pathway of compounds 1–4 was proposed, involving undergoing a transannular Diels–Alder cycloaddition. In the bioassay, the new compound 1 displayed significant inhibitory activities against the fish pathogens Streptococcus parauberis KSP28, oxytetracycline-resistant Streptococcus parauberis SPOF3K, and Photobacterium damselae FP2244, with MIC values of 9.1, 9.1, and 18.2 μg/mL, respectively. Furthermore, by conducting a luciferase reporter assay on rat liver Ac2F cells, compounds 1, 3, and 4 were evaluated for peroxisome proliferator-activated receptor (PPAR) transcriptional activity, and compound 3 showed selective PPAR-β agonist activity at a concentration of 10 μΜ.